2014
DOI: 10.1007/s11999-014-3506-0
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Cement Embolization After Vertebroplasty Requiring Pulmonary Wedge Resection

Abstract: Pulmonary cement embolism is a potentially serious complication of vertebroplasty. If a patient has chest pain or respiratory difficulty after the procedure, chest radiography and possibly advanced chest imaging studies should be performed immediately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 44 publications
0
31
0
2
Order By: Relevance
“…[25,2830] In our material no one patient, during the time of follow-up, did reveal any systemic complications. During follow-up 104 patients had X-ray study of lungs performed and in 2 of them small acrylic deposits were found.…”
Section: Discussionmentioning
confidence: 83%
“…[25,2830] In our material no one patient, during the time of follow-up, did reveal any systemic complications. During follow-up 104 patients had X-ray study of lungs performed and in 2 of them small acrylic deposits were found.…”
Section: Discussionmentioning
confidence: 83%
“…The patient in this case underwent a surgical embolectomy. Rothermich et al (14), on the other hand, reported on a case in which a 29-year-old man whose right lower lung lobe had infarcted owing to massive cement embolization, who was subjected to an open pulmonary wedge resection and embolectomy. The patient recovered from the embolectomy, but suffered chronic, persistent respiratory symptoms after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Due to respiratory failure thoracotomy with embolectomy and resection of the right lower lobe had been performed. Radical improvement was seen as a result of this treatment [9]. There are still no studies comparing the effectiveness of different treatment strategies.…”
Section: Review Of the Literaturementioning
confidence: 91%